The Effect of Capital Flows on Poverty Gap in West African Countries - Nwaobia, Appolos Nwabuisi; Ogbebor, Peter Ifeanyi; Adeyemi, Olanrewaju Micheal (International Journal of Economics and Financial Issues, 2025)
Poverty gap reduction is highly imperative because, it increases sustainable development among developing economies, increases economic growth, and enhances standards of living. Incidentally, studies have shown that poverty gap is increasingly widening and has become a challenging concern in West Africa. Studies have also shown that optimal utilization of capital flows can solve poverty gap problem in West Africa. This study examined the effect of capital flows on the poverty gap in West African countries. The study adopted an ex post facto research design and evaluated the effect of capital flows on macroeconomic performance in W/A for 33 years (1991 to 2023). Data were extracted from the World Development Index and the International Monetary Fund The validity and reliability of the data were premised on the global recognition of WDI as a reputable source. Descriptive and inferential System Generalized Method of Moments (GMM) statistics were used to analyze the data at the 0.05 level of significance. The study result showed that capital flows jointly had a significant effect on the poverty gap in West Africa. The study recommends that West African countries should consider optimally utilizing capital flows to invest in opportunities capable of bridging poverty gap in West Africa.